1981
DOI: 10.1093/bja/53.6.585
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of Labetalol-Induced Hypotension in the Anaesthetized Dog

Abstract: Central haemodynamic changes and regional blood flow were studied using the microsphere technique, during labetalol-induced hypotension in dogs anaesthetized with pentobarbitone and fentanyl. Labetalol 15 mg kg-1 decreased mean arterial pressure from an average of 88 mm Hg to 47 mm Hg. Mean pulmonary arterial pressure was unchanged. Cardiac output was reduced by decrease in stroke volume, while heart rate remained unchanged. Myocardial blood flow decreased approximately in parallel with left ventricular work. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Heart rate was only slightly and not significantly ( p = 0.2454) increased during labetalol therapy, as expected from its reversible antagonism activity at both α- and β-adrenoceptor [ 30 ]. This is in agreement with studies in humans and experimental dogs [ 3 , 9 , 20 ], and it is a considerable advantage, as compensatory tachycardia can delay the antihypertensive effect and increase myocardial oxygen consumption [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Heart rate was only slightly and not significantly ( p = 0.2454) increased during labetalol therapy, as expected from its reversible antagonism activity at both α- and β-adrenoceptor [ 30 ]. This is in agreement with studies in humans and experimental dogs [ 3 , 9 , 20 ], and it is a considerable advantage, as compensatory tachycardia can delay the antihypertensive effect and increase myocardial oxygen consumption [ 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…To date, all published literature describing use of labetalol in dogs is limited to experimental models. Studies in anaesthetized dogs demonstrated the hypotensive effect of labetalol at the dose of 0.1 to 15 mg/kg intravenously [ 6 , 20 ], and that a bolus of 100 mg followed by a constant rate infusion (CRI) of 30 mg/min produces a significative reduction in mean arterial pressure (MAP) without affecting intracranial pressure in experimental dogs weighing 27–33 kg [ 21 ]. Intravenous administration at doses of 0.1 to 3 mg/kg in anaesthetized dogs produced a dose-dependent reduction in blood pressure and myocardial contractility [ 2 ].…”
Section: Introductionmentioning
confidence: 99%